1982
DOI: 10.1093/sjaf/6.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Interim Models for Basal Area and Volume Projection of Uneven-Aged Loblolly-Shortleaf Pine Stands

Abstract: Equations are presented for estimating current volume, projected basal area, and projected volume for stands of loblolly-shortleaf (Pinus taeda L.-Pinus echinata Mill.) pine managed under the selection system. The independent variables are initial stand basal area and elapsed time. The estimates should provide a guide to the cubic-foot volume production that might be expected from stands on average sites (site indices 80-90 ft.), medium basal areas (30 to 70 sq. ft.) and time periods of 10 years or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Uneven-aged forest management, which is comprised of trees of three or more age classes, is not only a viable alternative to meet the demand of softwood timber products in the southern USA (Murphy and Farrar, 1982;Schulte and Buongiorno, 1998) but also valuable from aesthetic as well as environmental perspectives. The varying stand structure provides the diversity of habitat options to wildlife and offers protection against natural disturbances.…”
Section: Research Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Uneven-aged forest management, which is comprised of trees of three or more age classes, is not only a viable alternative to meet the demand of softwood timber products in the southern USA (Murphy and Farrar, 1982;Schulte and Buongiorno, 1998) but also valuable from aesthetic as well as environmental perspectives. The varying stand structure provides the diversity of habitat options to wildlife and offers protection against natural disturbances.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Uneven-aged forest stands are comprised of trees of three or more categories which vary in size, age and species (Murphy and Farrar, 1982). It is synonymously called all-aged or allsized management.…”
Section: Uneven-aged Forest Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…questionable, as it assumes that the Bertalanffy equation holds for populations as well as for individuals, and several empirical studies have reported negative coefficients (e.g., Moser andHall 1969, Murphy andFarrar 1982) where positive coefficients should hold. However, the equation continues to provide a good empirical model for compatible growth and yield estimates.…”
Section: Growth and Yield Equationsmentioning
confidence: 99%
“…Many studies regarding uneven-aged growth and yield have been conducted since (Burkhart and Tomé 2012;Choi and An 2016). For instance, Murphy and Farrar (1982) used the same method as Moser-Hall to develop models for the basal area and volume projection of uneven-aged loblolly-shortleaf pine forest stands. Also, Sullivan and Clutter (1972) developed compatible growth and yield models which consisted of a system of equations in to predict both volume and basal area (Clutter 1963).…”
Section: Introductionmentioning
confidence: 99%